Lingual mucosal ulceration with bony sequestration - Samsudin, Ahmad Dzulfikar; Jasni, Azmiza Syawani (Universiti Sains Islam Malaysia, 2022)
This case report describes a rare condition of lingual mucosal ulceration associated with bony sequestration following non-surgical lower molar tooth extraction of a healthy 58-year-old female patient. Clinically, she presented with a painful ulcer on the lingual aspect of the posterior mandible and noticed a sharp bone which caused irritation to the side of the tongue. The exposed bone was removed surgically, and the ulcer was completely healed. Thus, emphasizing the understanding of the causative factors of oral ulcers can help in giving a proper treatment plan.